Coccolith mass and morphology of different Emiliania huxleyi morphotypes: A critical examination using Canary Islands material - Linge Johnsen, Simen Alexander (PLoS One, 2020)
Different morphotypes of the abundant marine calcifying algal species Emiliania huxleyi are commonly linked to various degrees of E. huxleyi calcification, but few studies have been done to validate this assumption. This study investigated therefore whether E. huxleyi morphotypes can be related to coccolithophore calcification and coccolith mass. Samples from January (high productivity) and September (low productivity) 1997 at an open ocean and a coastal site near the Canary Islands were analysed using a combination of thickness measurements (Circular Polarizer Retardation estimates (CPR) method), Scanning Electron Microscope imaging, and Markov Chain Monte Carlo (MCMC) models. Mean E. huxleyi coccolith mass varied from a maximum of 2.9pg at the open ocean station in January to a minimum of 1.7pg in September at both stations. In contrast, overall calcite produced by E. huxleyi (assuming 23 coccoliths/cell) varied from a maximum of 2.6 μgL(-1) at the coastal station in January to a minimum of 0.5 μgL(-1) in September at the open ocean site. The relative abundance of “Overcalcified” Type A, Type A, Group B and malformed coccoliths was determined from SEM images. The mean coccolith mass of “Overcalcified” Type A was 2.0pg using the CPR-method, while mean mass of Type A and Group B coccoliths was determined using coccolith length measurements from SEM images and MCMC models relating thickness measurements to morphotype relative abundance. Type A cocccolith mass varied from a 1.6pg to 2.6pg and Group B coccolith mass varied from 1.5pg to 2.0pg. These results demonstrate that the coccolith mass of Type A, “Overcalcified” Type A, and Group B do not differ systematically and there is no systematic relationship between relative abundance of a morphotype and the overall calcite production of E. huxleyi. Therefore, morphotype appearance and relative abundance can not be uniformly used as reliable indicators of E. huxleyi calcification or calcite production.